2020
DOI: 10.1007/s11356-020-08047-1
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of the ultrafiltration of real oil-contaminated (produced) water with pre-ozonation and/or with TiO2, TiO2/CNT nanomaterial-coated membrane surfaces

Abstract: In the present study, commercial PES, PVDF, PTFE ultrafilter membranes, and two different nanomaterial (TiO 2 and TiO 2 /CNT composite)-covered PVDF ultrafilter membranes (MWCO = 100 kDa) were used for the purification of an industrial oilcontaminated (produced) wastewater, with and without ozone pretreatment to compare the achievable fouling mitigations by the mentioned surface modifications and/or pre-ozonation. Fluxes, filtration resistances, foulings, and purification efficiencies were compared in detail. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 58 publications
0
14
1
Order By: Relevance
“…Although WO 3 did not live up to our expectations in the present study, the investigation of three‐component composites is recommended as they are promising in achieving low band gap and suppressed recombination ratio at the same time. For example, graphene oxides and CNTs are also promising for use as the third component of a TiO 2 /BiVO 4 or other composite systems, as they can improve the homogeneity and/or the antifouling properties of the surfaces and may also suppress the charge carrier recombination 38,45,47 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although WO 3 did not live up to our expectations in the present study, the investigation of three‐component composites is recommended as they are promising in achieving low band gap and suppressed recombination ratio at the same time. For example, graphene oxides and CNTs are also promising for use as the third component of a TiO 2 /BiVO 4 or other composite systems, as they can improve the homogeneity and/or the antifouling properties of the surfaces and may also suppress the charge carrier recombination 38,45,47 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, photocatalytic membrane reactors (PMRs)—equipped with photocatalyst‐modified membrane surfaces—are able to eliminate organic fouling contaminants and to recover the flux via an efficient and chemical‐free way that is based on the photocatalytically generated oxidative species 40,41,43,44 . Immobilization of photocatalytic nanoparticles can be carried out by physical deposition, 37,45,46 cross‐linking, 47 in situ precipitation, 33 dip coating, 48 grafting, 35 blending, 34,39,43,49 and so forth. There are numerous studies in the literature that proved the beneficial properties of these photocatalytic membranes—such as lower filtration resistances, reduced fouling, increased flux, higher separation efficiency, advanced flux recovery, and self‐cleaning ability—during the filtration of wastewaters containing dyes, 46,47 oils, 33–38,45–49 or other hydrocarbons 34,35,46 …”
Section: Introductionmentioning
confidence: 99%
“…Surfactants minimise oilwater interfacial stress when the oil mixture is separated to the oil-water interface, thus reducing the energy needed for droplet breakup [46][47][48] Yet, the presence of surfactant will modify emulsion properties, including interfacial stress, droplet size and charge, and membrane properties, such as wetting and surface charge. Membrane properties such as surface charge [47,48] and water and oil hydrophilicity and oleophilicity [49,50] can be altered by surfactants. The surfactant's ability varies based on the form and composition of both oil and the surfactant types, mixture conditions, temperature and phase composition [51,52].…”
Section: Effect Of Surfactantsmentioning
confidence: 99%
“…Feng et al [61] prepared a TiO 2 -deposited CNT membrane and showed remarkable enhancement in the capacitive deionization performance. Veréb et al [62] illustrated the intensification of the ultrafiltration of real oil-contaminated water with a pre-ozonated/TiO 2 /CNT nanomaterial-coated membrane. There is still a lack of studies on the performance of TNT and CNT hybrid fillers in the polymer matrix (e.g., CTA) for gas separation.…”
Section: Introductionmentioning
confidence: 99%